Volatility of the Polish zloty against major international currencies compared to other Central and Eastern European currencies in 2004-2010 and 2011-2019 - Czaja, Jarosław (Zmienność złotego względem głównych walut międzynarodowych w porównaniu z innymi walutami Europy Środkowej i Wschodniej w latach 2004-2010 i 2011-2019, 2020)
Exchange rate volatility reached significant levels as one of the problems of the 2008 financial crisis, which showed that the market mechanism, even internationally, is not always conducive to restoring stability in various aspects. The aim of the paper is to compare the exchange rate volatility of the Polish zloty and several other currencies (mainly in the Central European region) against major international currencies such as the US dollar, British pound, euro and Swiss franc before and after the crises in 2004-2010 and 2011-2019. A review of the existing literature aimed to show some effects of exchange rate volatility on the economy. An analysis was made by comparing two periods (2004-2010 and 2011-2019). Exchange rate volatility was calculated as a standard deviation of the twenty-day moving average (by market days). Exchange rate volatility became much lower in the second examined period (in the European Union countries, including Poland) after the strong institutional (activities and interventions of central banks and governments) support started because of the financial crisis in 2008. There was a decrease in currency volatility in the European Union countries, including Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 49-64